Bem-estar pessoal de pais e filhos e seus valores aspirados. - Sarriera, Jorge Castellá (2016)
SARRIERA, Jorge Castellá; XIMENES, Verônica Morais; BEDIN, Lívia; RODRIGUES, Anelise Lopes; SCHÜTZ, Fabiane Friedrich; MONTSERRAT, Carme; SILVA, Caroline Lima. Bem-estar pessoal de pais e filhos e seus valores aspirados. Aletheia, Canoas - RS, v. 37, p.91-104, jan./abr. 2012.